Penerapan CTL (Contextual Teaching and Learning) dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Endah Tri Priyatni (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: Contextual teaching is a strategy that can help teachers in making relation between contents of subjects and real world context. It is also increase students’ motivation in bridging between their knowledge and the implementation to their ordinary life. The strategy is appropriate to implement in elementary school level with concrete operational thinking level. This article describes the implementation of contextual teaching strategy in teaching Indonesia language at elementary school level.